A Review of Tip Clearance in Propeller, Pump and Turbine - Yabin Liu; Lei Tan; Binbin Wang (Energies, 2018)
Propellers, pumps, and turbines are widely applied in marine equipment, water systems, and hydropower stations. With the increasing demand for energy conservation and environmental protection, the high efficiency and the stable operation of pumps and turbine have been drawing great attention in recent decades. However, the tip clearance between the rotating impeller and the stationary shroud can induce leakage flow and interact with the main stream, introducing complex vortex structures. Consequently, the energy performance and the operation stability of pumps and turbines deteriorate considerably. Constant efforts are exerted to investigate the flow mechanism of tip-clearance flow and its induced influence on performance. However, due to various pump and turbine types and the complexity of tip-clearance flow, previous works are usually focused on a specific issue. Therefore, a systematic review that synthesizes the related research is necessary and meaningful. This review investigates related research in the recent two decades in the perspectives from fundamental physics to engineering applications. Results reveal the vortex types, trajectory, evolution, and cavitation behaviors induced by tip-clearance flow. It is concluded that the influence characteristics of tip clearance on energy performance are closely related to the machinery type. Tip-clearance size and tip shape are found to be crucial parameters for tip-leakage vortex (TLV). The proposed optimization schemes are also demonstrated to provide inspiration for future research. Overall, this review article provides a coherent insight into the characteristics of tip-clearance flow and the associated engineering-design applications. On the basis of these understandings, comments on conducted research and ideas on future research are proposed.